USING GAME IN TEACHING BUSINESS ENGLISH - Игнатьева, Ольга; Ткаченко, Людмила; Ланских, Елена (SWorldJournal, 2021)
This article is devoted to the investigation of the problem of teaching Business foreign language and its optimization in the learning process. The ways of using business game in higher educational establishments of Ukraine are characterized.